2011
DOI: 10.1016/j.rbmo.2010.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the new legislation and single-embryo transfer policy in Turkey on assisted reproduction outcomes: preliminary results

Abstract: New legislation concerning assisted reproduction treatments was introduced in Turkey in March 2010 in order to reduce the number of multiple pregnancies. This new legislation limits the number of embryos to be transferred to one under 35 years of age in the first or second treatment cycles and to two in the third or further cycles or for 35 and older ages. The aim of this multicentre study was to investigate the effect of this new law on clinical pregnancy and multiple pregnancy rates. Outcomes were compared i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Despite the more than tenfold rise in the use of eSET, both IRs (18% vs. 18%) and clinical PRs (32% vs. 31%) were not statistically different between these two time periods, while the multiple gestation rate dropped significantly from 31% to 23%. Multiple subsequent studies have reproduced these findings (10,16,18,22,50,51).…”
Section: Figurementioning
confidence: 72%
“…Despite the more than tenfold rise in the use of eSET, both IRs (18% vs. 18%) and clinical PRs (32% vs. 31%) were not statistically different between these two time periods, while the multiple gestation rate dropped significantly from 31% to 23%. Multiple subsequent studies have reproduced these findings (10,16,18,22,50,51).…”
Section: Figurementioning
confidence: 72%
“…In 2010, turkey introduced new legislation mandating Set in women less than 35 years of age in the first or second cycle of treatment and limiting clinics to the transfer of two embryos in the third or subsequent treatment cycles and in women over the age of 35 years (Kultursay et al, 2015). Since the implementation of this policy, preliminary results reported from a small multi-centre study have shown a significant reduction in mpr, with a modest downward trend in clinical pregnancy rate (Cpr) from 39.9 % to 34.5 %, although this was not statistically significant (Kutlu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the clinical problems, multiple gestations also cause major economic and social consequences (Lee et al, 2006;Kalu et al, 2008;Paperstraten et al, 2008;Gerris, 2009;Kutlu et al, 2011;Martini et al, 2011;Lawlor & Nelson, 2012; Practice Committee of American Society for Reproductive Medicine, 2012). High costs are related to maternal hospitalization, cesarean section and neonatal intensive care, the most frequent (Kalu et al, 2008; Practice Committee of American Society for Reproductive Medicine, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term costs are associated with chronic diseases, rehabilitation and investment in special education (Practice Committee of American Society for Reproductive Medicine, 2012). For these reasons, experts have tried to reduce the number of embryos transferred per cycle in order to reduce multiplicity without affecting pregnancy rate (Kalu et al, 2008;Kutlu et al, 2011; Practice Committee of American Society for Reproductive Medicine, 2012). In some places, guidelines have been created to suggest the number of embryos to be transferred according to patient age, embryo quality and failure in previous proceedings (Kalu et al, 2008;Bromer et al, 2009;Kutlu et al, 2011; The Practice Committee of the American Society of Reproductive Medicine and the Practice Committee of the Society for Assisted Reproductive Technology, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation